NEW CONCEPTS IN BLADDER SENSATION AND URINARY URGENCY - Naimi, Hameeda A (Curr Bladder Dysfunct Rep, 2018)
PURPOSE OF REVIEW: The purpose of this review is to summarize the current state of knowledge regarding the evaluation and measurement of urinary urgency and bladder sensation. RECENT FINDINGS: New technologies have been developed to improve our diagnostic capabilities in urinary urgency and bladder sensation. Recent developments include MRI-based neuroimaging and novel tablet-based sensation meters that can be used during urodynamics as well as during oral hydration. SUMMARY: Commonly used metrics for urinary urgency and bladder sensation include the use of validated surveys/void diaries and standardized verbal sensory thresholds during urodynamics. However, these metrics are highly subjective and prone to significant bias. There has been an evolution in evaluation metrics ranging from the use of reflex testing to electrical perception testing to the use of neuroimaging and the development of sensation meters. Neuroimaging allows for mapping of specific brain areas involved in the different phases of voiding and provides an anatomic basis for different forms of overactive bladder. The sensation meter allows for generation of real-time sensation-capacity curves which enables easy and objective comparison between patients as well as potential sub-typing of different forms of overactive bladder. In addition, new research supports the concept of differing forms of urgency and the use of novel patient-derived terminologies for urinary urgency and bladder sensation.